Effect of Gluten Free Diet Adherence on Growth Parameters of Children with Celiac Disease: A Follow Up of Patients in Al-Bieda Medical Center From 2005 to 2016 - Kamala Yonis; Mabrouka Bofarraj; Aisha Muhammed; Salema Qowaider; Hawwa Othman (AlQalam Journal of Medical and Applied Sciences, 2021)
Celiac disease (CD) is an autoimmune disease that develops in patients with a genetic predisposition, incurring a susceptibility to gluten-containing foods such as barley, wheat, and rye. The elimination of gluten from the diet is the main therapeutic approach and usually leads to clinical and laboratory improvement. This the study was designed to determine the role of dietary compliance and adherence effect of gluten free diet (GFD) among celiac disease patient. Thirty-six patients with Celiac disease (CD) who were confirmed by duodenal biopsy included in the study. The mean age of patients at diagnosis was 7.94. 69.2% of the patients aged ≤6 year were compliers, 56.5% of patients aged > 6years were compliers. 41.7% of GFD complaint patients were stunted. however,30.4% of GFD non-compliant group were stunted as well. FTT was observed in 26% and 34.8% of the GFD compliant group and GFD non-compliant group respectively. complications found to be more common in GFD non complaint group (69.6 %) in compare to the GFD complaint group (15.4 %). the difference was statistically significant P-Value (0.000). we conclude that adherence to the GFD has a significant positive impact on health of children with CD, children with CD should be encouraged and regularly followed in terms of compliance with the GFD.